1999
DOI: 10.1002/(sici)1096-9896(199905)188:1<14::aid-path323>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite instability in sporadic colorectal carcinoma is not an indicator of prognosis

Abstract: Fifty sporadic colorectal carcinomas diagnosed in 1991 were analysed for microsatellite instability at four loci. Five of 50 (10 per cent) tumours showed replication errors (RERs) at two or more loci and were classed as RER‐positive (RER+). A further five showed RERs at one locus only. A significant association (Fisher exact test) was found between RER+ tumours and location in the proximal colon, exophytic shape, size >5 cm, histological margin, lymphoid reaction, and near‐diploid DNA content. There was no sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
28
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 14 publications
5
28
0
1
Order By: Relevance
“…Patients with colorectal carcinoma, coincident with germ-line mutation in mismatch repair genes, tend to develop near-diploid cancers with few chromosomal aberrations, often without p53 mutation, and this is the pattern observed here Bocker et al, 1996;Cottu et al, 1996;Feeley et al, 1999;Forster et al, 1998;Ionov et al, 1993;Konishi et al, 1996;Lothe et al, 1993;Olschwang et al, 1997;Remvikos et al, 1995;Schlegel et al, 1995). Previous studies have suggested that loss of p53 function is associated with chromosomal instability, favouring the development of aneuploidy, polyploidy, chromosomal breaks and ampli®cation (Bischo et al, 1990;Bou er et al, 1995;Carder et al, 1993;Donehower et al, 1995;Fukasawa et al, 1997;Harvey et al, 1993;Livingstone et al, 1992;Meling et al, 1993;Purdie et al, 1994;Tsukada et al, 1993;Yin et al, 1992).…”
supporting
confidence: 52%
“…Patients with colorectal carcinoma, coincident with germ-line mutation in mismatch repair genes, tend to develop near-diploid cancers with few chromosomal aberrations, often without p53 mutation, and this is the pattern observed here Bocker et al, 1996;Cottu et al, 1996;Feeley et al, 1999;Forster et al, 1998;Ionov et al, 1993;Konishi et al, 1996;Lothe et al, 1993;Olschwang et al, 1997;Remvikos et al, 1995;Schlegel et al, 1995). Previous studies have suggested that loss of p53 function is associated with chromosomal instability, favouring the development of aneuploidy, polyploidy, chromosomal breaks and ampli®cation (Bischo et al, 1990;Bou er et al, 1995;Carder et al, 1993;Donehower et al, 1995;Fukasawa et al, 1997;Harvey et al, 1993;Livingstone et al, 1992;Meling et al, 1993;Purdie et al, 1994;Tsukada et al, 1993;Yin et al, 1992).…”
supporting
confidence: 52%
“…Salahshor et al (1999) found an obvious trend towards a better outcome of their MSI-H collective, but this was not statistically significant. Feeley et al (1999) could not see any impact of microsatellite status on patients' survival at all, but the validity of this study is limited by the low number of MSI-H cases. In summary, however, most studies revealed a longer disease-free and overall survival for patients with MSI-H CRC compared to MSS CRC (Watson et al, 1998;Gryfe et al, 2000;Samowitz et al, 2001).…”
mentioning
confidence: 75%
“…3,[8][9][10][11] This low mutational incidence is also accompanied by a decreased incidence of loss of heterozygosity (LOH), 1,3,12 which is reflected at the cytogenetic level in frequent (pseudo)diploidy. [13][14][15][16] The PTEN tumor suppressor gene is located on chromosome 10q23, consists of 9 exons and encodes a protein product of 403 amino acids with phosphatidylinositol, tyrosine and serine/threonine protein phosphatase activity. [17][18][19] Its relation with cancer appears to be centered mainly on its capability to antagonize the phosphatidylinositol 3,4,5-trisphosphate (PIP3) kinase activity, modulating negatively the PIP3-Akt signaling pathway.…”
mentioning
confidence: 99%